S100A11 is involved in the regulation of the stability of cell cycle regulator p21CIP1/WAF1 in human keratinocyte HaCaT cells. (27th June 2013) - Foertsch, Franziska; Teichmann, Nicole; Kob, Robert; Hentschel, Julia; Laubscher, Ulrike; Melle, Christian
Abstract : The cyclin‐dependent kinase inhibitor p21 CIP1/WAF1 is a regulatory factor of the cell cycle. Its transcriptional activation and protein stability are tightly controlled by several distinct mechanisms. S100A11 is a member of the S100 family of Ca 2+ ‐binding proteins involved in several biological processes, including cell cycle progression and signal transduction. In the present study, we show that down‐regulation of S100A11 results in the reduction of p21 protein in human HaCaT keratinocytes. It appears that a ubiquitin‐independent proteasomal degradation process is involved in p21 degradation in S100A11 down‐regulated cells. The application of a proteasome inhibitor stabilized p21 protein in these cells. Analysis of distinct signal transduction pathways revealed a disturbed phosphatidylinositol‐3‐kinase/Akt pathway after S100A11 knockdown. We determined that the glycogen synthase kinase‐3, which is negatively regulated by phosphatidylinositol 3‐kinase/Akt, was activated in cells possessing knocked‐down S100A11 and appears to be involved in p21 protein destabilization. The application of a specific inhibitor of glycogen synthase kinase 3 resulted in an increase of the p21 protein level in S100A11 down‐regulated HaCaT cells. Glycogen synthase kinase 3 is able to phosphorylate p21 at T57, which induces p21 proteasomal turnover. Mutation of the glycogen synthase kinase 3 site threonine 57 into alanine (T57A) stabilizes p21 in HaCaT cells lacking S100A11. Beside decreased p21 protein, down‐regulation of S100A11 triggered the induction of apoptosis in HaCaT cells. These observations suggest that S100A11 is involved in the maintenance of p21 protein stability and appears to function as an inhibitor of apoptosis in human HaCaT keratinocyte cells. Thus, the data shed light on a novel pathway regulating p21 protein stability. Abstract : The cyclin‐dependent kinase inhibitor p21 CIP1/WAF1 regulates the cell cycle. Down‐regulation of the Ca 2+ ‐binding protein S100A11 deregulates PI3K/Akt pathway followed by activating GSK3 that mediates the degradation of p21 by phosphorylation at Thr57 which triggers a ubiquitin‐independent proteasomal mechanism. Hence, S100A11 seems to be involved in regulation of the p21 protein stability by controlling the PI3K/Akt‐GSK3 – axis.